Early extubation is associated with improved early outcome after extracardiac total cavopulmonary connection independently of duration of cardiopulmonary bypass. (27th April 2018) - Ovroutski, Stanislav; Kramer, Peter; Nordmeyer, Sarah; Cho, Mi-Young; Redlin, Matthias; Miera, Oliver; Photiadis, Joachim; Berger, Felix
Abstract: OBJECTIVES: Strict patient selection, short cardiopulmonary bypass (CPB) time and short mechanical ventilation are well-recognized aspects of optimizing the postoperative course after total cavopulmonary connection. In this study, we evaluated the influence of our early postoperative extubation strategy in our population of Fontan patients over the past 2 decades. METHODS: Early postoperative course was evaluated retrospectively in 211 consecutive patients, who were selected for total cavopulmonary connection in our institution between 1995 and 2015. We analysed postoperative haemodynamic parameters and early outcome after surgery (mortality and length of hospital stay) according to preoperative patient characteristics, duration of CPB and duration of mechanical ventilation. To investigate the influence of mechanical ventilation, the cohort was subdivided into a 'fast-track' extubation group (≤6 h ventilation, n = 59) and a prolonged ventilation group (>6 h ventilation, n = 152). RESULTS: In the entire cohort, duration of CPB did not correlate with duration of mechanical ventilation ( P = 0.1), and it did not differ between both groups ( P = 0.3). Patients in the fast-track group showed significantly better haemodynamics with higher mean arterial pressure and lower mean pulmonary artery pressure at 6, 24 and 48 h postoperatively when compared with the prolonged ventilation group ( P = 0.02–0.001). In multivariable analysis, longer mechanical ventilation, but not duration of CPB, was independently associated with length of hospital stay. CONCLUSIONS: Early weaning from mechanical ventilation correlates with improved early Fontan haemodynamics, whereas early outcome is unrelated to duration of CPB. This indicates that early extubation may represent a principal strategy for improving early results after total cavopulmonary connection.